Comparative Analysis of Cyber Sovereignty: Case from Indonesia and Iran - Lidia Tri Chris Nia Wati; Mahmud Syaltout Syahidullhaq; Bimantoro Kushari Pramono (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
Talking technological advancements cannot be separated from the cyber world, which is now easily accessible to everyone. The cyber-world can also determine the sovereignty of a country. This research aims to find out how sovereign the cyber world is between Iran and Indonesia. To find out the differences in the sovereignty of the two countries, the researcher uses the Euro-Cyber Sovereignty Approach, and the theory used is the Three-Perspective Theory. Open-source intelligence (OSINT) data can be retrieved using Maltego, an Excel query, and SEOquake. The researchers found three types of data: cyber applications, cyber-infrastructure, and cyber core. The size of the two countries' cyber sovereignty can be seen from these data. Between Iran and Indonesia, the country with the most cyber sovereignty is Indonesia. Indonesia has 46.7% cyber sovereignty, while Iran has 46.38%. The two countries are increasing cyber sovereignty in different ways: Iran tends to increase cyber offensives, while Indonesia is increasing bilateral and multilateral cooperation with major countries.